1984
DOI: 10.1002/ajmg.1320190222
|View full text |Cite
|
Sign up to set email alerts
|

Linkage analysis in lattice corneal dystrophy

Abstract: Two kindreds of lattice corneal dystrophy (LCD) [McKusick, 1983, catalog No. 12220] were studied for linkage. Fifty-one relatives were examined clinically, and 27 affected and 24 normal persons were ascertained. Tight linkage could be excluded for 15 informative markers with LOD scores of less than -2.0. The largest positive LOD score was 0.56 at 0 = 0.17 for linkage between haptoglobin and LCD. Combined with a previous study, the combined LOD score is 0.96.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
2

Year Published

1984
1984
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 2 publications
0
26
0
2
Order By: Relevance
“…Electrophysiologic studies confirm loss of ganglion cell function predominantly from central retina, but not the exclusive result of either parvocellular or magnocellular cell loss. 111 One study of a large pedigree of German descent suggested linkage of the gene responsible for dominant optic atrophy with the Kidd blood group antigen, subsequently localized to chromosome 18q12 112,119 (see the accompanying article in this volume on the molecular genetics of optic neuropathies). Further study of this family refined the chromosomal locus to a 3-cM region at 18q12.…”
Section: Dominant Optic Atrophymentioning
confidence: 99%
“…Electrophysiologic studies confirm loss of ganglion cell function predominantly from central retina, but not the exclusive result of either parvocellular or magnocellular cell loss. 111 One study of a large pedigree of German descent suggested linkage of the gene responsible for dominant optic atrophy with the Kidd blood group antigen, subsequently localized to chromosome 18q12 112,119 (see the accompanying article in this volume on the molecular genetics of optic neuropathies). Further study of this family refined the chromosomal locus to a 3-cM region at 18q12.…”
Section: Dominant Optic Atrophymentioning
confidence: 99%
“…Denmark has the highest reported frequency (Kjer et al, 1996). The disease shows 98 % penetrance but has a clinically variable phenotype both within and between families (Kivlin et al, 1983). Symptoms include a bilateral, slow visual loss ranging from mild to severe, abnormalities of colour vision (particularly tritanopia) and central or centrocaecal field defects.…”
Section: Copyright © 2001 S Karger Ag Baselmentioning
confidence: 99%
“…(McKusick no. 16540) is also possibly linked to Jk (Kivlin et al, 1984). However, since the maximum lod score is only slightly above 2, additional data will be needed for any assignment.…”
Section: Page 23mentioning
confidence: 99%